EFEK PENINGKATAN SUHU TERHADAP JUMLAH LEUKOSIT IKAN NILA (Oreochromis niloticus) (The Effect of Temperature Increase on Leukocyte Count of Nile Tilapia (Oreochromis niloticus)) - Nauval Gibran Lubis; Sugito Sugito; Zuhrawati Zuhrawati; Zuraidawati Zuraidawati; Nuzul Asmilia; Hamny Hamny; Ummu Balqis (Jurnal Medika Veterinaria, 2016)
The aim of this research was to find out the effect of water temperature increase on leucocyte count of nile tilapia. The blood sample from 9 tilapia with weigh of 40-50 g were used in this study. The research was conducted using completely randomized design (CRD) with 3 treatments and 3 replications. Treatment P1 as a control with aquarium temperature was maintained at 29±1 C. Water temperature in treatment P2 and P3 was maintained at 32±1 C and 35±1 C respectively. The aquarium size in each treatment group was 80x60x40 cm with height of water 30 cm. The treatment was done for 15 days and on day 16th, the blood were collected from caudal vein. Data were analyzed with analysis of variance (Anova) and followed with Duncan's multiple range test. The result showed that total leucocyte count (x 105/mm3) of nile tilapia in group P1, P2, and P3 were 3.08±0.88, 1.70±0.52, and 1.69±0.20 respectively. lts showed that an increase in temperature significantly affect (P0.05) the leucocyte count of nile tilapia. The conclusion of this research is the increase in water temperature in aquarium decrease the leucocyte count of nile tilapia.